2001
DOI: 10.1034/j.1399-6576.2001.450108.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative rectal diclofenac versus paracetamol for tonsillectomy: effects on pain and blood loss

Abstract: Preoperative rectal diclofenac offers no advantage over paracetamol with respect to postoperative analgesia in tonsillectomy patients but increases intraoperative blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 22 publications
3
43
2
3
Order By: Relevance
“…Morton and O'Brien demonstrated that concurrent administration of diclofenac in children receiving patient-controlled analgesia (PCA) morphine has a highly significant morphinesparing effect, although they failed to demonstrate any extra additive effect of paracetamol [14]. Our finding is similar to those of other investigators who demonstrated a reduction of opioid consumption after diclofenac and paracetamol [13][14][15]. Schmidt and his group reported that pre-operative rectal diclofenac offers no advantage over paracetamol with respect to pain score and the postoperative pethidine consumption in patients undergoing tonsillectomy [15].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Morton and O'Brien demonstrated that concurrent administration of diclofenac in children receiving patient-controlled analgesia (PCA) morphine has a highly significant morphinesparing effect, although they failed to demonstrate any extra additive effect of paracetamol [14]. Our finding is similar to those of other investigators who demonstrated a reduction of opioid consumption after diclofenac and paracetamol [13][14][15]. Schmidt and his group reported that pre-operative rectal diclofenac offers no advantage over paracetamol with respect to pain score and the postoperative pethidine consumption in patients undergoing tonsillectomy [15].…”
Section: Discussionsupporting
confidence: 81%
“…Our finding is similar to those of other investigators who demonstrated a reduction of opioid consumption after diclofenac and paracetamol [13][14][15]. Schmidt and his group reported that pre-operative rectal diclofenac offers no advantage over paracetamol with respect to pain score and the postoperative pethidine consumption in patients undergoing tonsillectomy [15]. Similarly, Rømsing and his colleagues demonstrated that diclofenac was no more effective than high-dose paracetamol for analgesia in patients following tonsillectomy [16].…”
Section: Discussionsupporting
confidence: 81%
“…22 Interestingly, in this study a greater estimated intraoperative blood loss and increased loss of haemoglobin until 24 h was also observed in the conventional NSAID group. The reason for this may well be the reduced production of the coagulation activator thromboxane B 2 , which is biosynthesized by COX-1.…”
Section: Discussionmentioning
confidence: 55%
“…Findings were in accordance with finding of Schmidt and his group who reported that preoperative rectal diclofenac offers no advantage over paracetamol with respect to pain score and the postoperative pethidine consumption in patients undergoing tonsillectomy. [21] Similarly, Rømsing and his colleagues demonstrated that diclofenac was no more effective than high-dose paracetamol for analgesia inpatients following tonsillectomy [22] Viitanen et al demonstrated that the total morphine used was significantly less in groups receiving paracetamol, ibuprofen or their combination compared to those receiving placebo for paediatric Section: Anaesthesia adenoidectomy. [23] Morton and O'Brien demonstrated that concurrent administration of diclofenac sodium in children receiving patientcontrolled analgesia(PCA) morphine has a highly significant morphine sparing Effect.…”
Section: Discussionmentioning
confidence: 99%